Structural status of vocational schools in Turkiye and Germany: A comparable case study - Cetin, Emircan (Cita konsultindo, 2025)
Due to the significant impact and contribution of vocational education and training (VET) in economic growth and development, policy makers and stakeholders prioritize VET in their economic goals. Although there are many university and vocational school (MYO) graduates in Turkiye, there is a shortage of trained personnel especially in technical and vocational fields. The number of MYO has reached a total of 1003 and students number is 2.82 millions compared to the vocational schools of 211 in Germany. The employment rate of bachelor's degree graduates was 75.6%, while this rate was 67.3 % for MYO graduates in Turkiye. Duration to find a job is about 15 months, compared to only 4 months in European countries. The German VET model is recognized worldwide as a fundamental and effective model for VET. The main reason is that it is a practice and model that combines theory and practice, learning and work, classroom and companies. In Turkiye, some efforts to improve the quality and effectiveness of MYOs and the technical high schools have increased in recent years. It is aimed for students in the relevant programs to work full-time in an company for one semester in the last year of their education period in order to improve their professional skills and experiences. Structural change and practices similar to the system in Germany might be considered based on socio-economic conditions in Turkiye and their experiences could be useful for MYOs.